From adhesion complex to signaling hub: the dual role of dystroglycan - Sciandra, Francesca; Bozzi, Manuela; Bigotti, Maria Giulia (Frontiers in Molecular Biosciences, 2023)
Dystroglycan (DG) is a transmembrane protein widely expressed in multiple cells and tissues. It is formed by two subunits,  and -DG, and represents a molecular bridge between the outside and the inside of the cell that is essential for the mechanical and structural stability of the plasma membrane. The  subunit is a cell-surface protein that binds the extracellular matrix (ECM) and is tightly associated with the plasma membrane via a non-covalent interaction with the -subunit, which in turn is a transmembrane protein that binds to the cytoskeletal actin. DG is a versatile molecule acting not only as a mechanical building block,but also as a modulator of outside-inside signalling events. The cytoplasmic domain of -DG interacts with different adaptor and cytoskeletal proteins that function as molecular switches for the transmission of ECM signals inside the cells. These interactions can modulate the involvement of DG in different biological processes, ranging from cell growth and survival to differentiation and proliferation/regeneration.Although the molecular events that characterize the signalling through the ECM-DG-cytoskeleton axis are still largely unknown, in recent years a growing list of evidence is starting to fill the gaps in our understanding of the role of DG in signal transduction. This mini-review represents an update of recent developments uncovering the dual role of DG as adhesion and signalling molecule that might inspire new ideas for the design of novel therapeutic strategies for pathologies such as muscular dystrophy, cardiomyopathy and cancer, where the DG signalling hub plays important roles.